Experimental Investigation of Al2O3 - Water Ethylene Glycol Mixture Nanofluid Thermal Behaviour in a Single Cooling Plate for PEM Fuel Cell Application. (November 2015) - Zakaria, Irnie; Mohamed, W.A.N.W.; Mamat, A.M.I. Bin; Saidur, R.; Azmi, W.H.; Mamat, Rizalman; Talib, S.F.A.
Abstract: Thermal enhancement through application of nanofluid coolant in a single cooling plate of Proton Exchange Membrane (PEM) fuel cell was experimentally investigated in this paper. The study focuses on low concentration of Al2 O3 dispersed in Water - Ethylene Glycol mixtures as coolant in a carbon graphite PEM fuel cell cooling plate. The study was conducted in a cooling plate size of 220 mm x 300 mm with 22 parallel mini channels and large fluid distributors. The mini channel dimensions are 100 mm x 1 mm x 5 mm. A constant heat load of 100W was applied by a heater pad that represents the artificial heat load of a single cell. Al2 O3 nanoparticle used was 0.1 and 0.5 vol % concentration which was then dispersed in 50:50 (water: Ethylene Glycol) mixture. The effect of different flow rates to heat transfer enhancement and fluid flow represented in Re number range of 20 to 120 was observed. Heat transfer was improved up to 13.87% for 0.5 vol % Al2 O3 as compared to the base fluid. However the pressure drop also increase which result in pumping power increment up to 0.02W. The positive thermal results implied that Al2 O3 nanofluid is a potential candidate for future applications in PEM fuel cell thermal management.